2021
DOI: 10.1108/ejmbe-05-2021-0155
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors and outcomes of trust in mobile supply chains

Abstract: PurposeThe main purpose of this paper is the identification of the conceptualization of trust as well as its factors and outcomes in interorganizational relations in mobile supply chains (MSCs) in which multiple stakeholders collaborate.Design/methodology/approachThe authors first used a comprehensive literature review to extract related factors and outcomes of trust. Second, the authors conducted semi-structured interviews in chemical and pharmaceutical companies in Germany. These organizations stand out as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…As shown in Figure 4, three critical strategies qualify for building a safe and secure environment to manage the tension between trust and confidentiality. Each of these elements have been mentioned in the literature as a factor for building or maintaining trust [4,27,29,41]. However, the results of this study show that partners need to employ these three strategies simultaneously to manage the tension between trust and confidentiality.…”
Section: Strategies For Managing the Tension Between Trust And Confid...mentioning
confidence: 71%
See 4 more Smart Citations
“…As shown in Figure 4, three critical strategies qualify for building a safe and secure environment to manage the tension between trust and confidentiality. Each of these elements have been mentioned in the literature as a factor for building or maintaining trust [4,27,29,41]. However, the results of this study show that partners need to employ these three strategies simultaneously to manage the tension between trust and confidentiality.…”
Section: Strategies For Managing the Tension Between Trust And Confid...mentioning
confidence: 71%
“…These results contradict with previous studies [103,104] which concluded that exchange of sensitive information is essential for cultivating long-lasting trustful relationship. This illustrates that the relationship between information sharing and trust is complicated and two-way [41,105].…”
Section: Grey-box Scenariomentioning
confidence: 98%
See 3 more Smart Citations